Hydridation and oxidation behaviors of tantalum hydride during milling process. (February 2019) - Lee, Ji-Eun; Yoon, Jin-Ho; Lee, Chan-Gi; Park, Ji-Hwan; Park, Il-Kyu
Abstract: The effect of ethanol addition during milling on the milling performances of Ta-hydride powders was investigated for hydride and dehydride processes during Ta recycling process. As the Ta-hydride was milled in a conventional dry atmosphere, Ta2 O was dominantly formed due to the increased temperature of the Ta-hydride pieces because they were rubbed against each other and crushed by the ring mill system. However, with the addition of ethanol solvent, the ratio of the Ta2 H phase increased compared to the Ta2 O phase, and the size of the powders reduced and became more uniform. These were attributed to the enhanced hydride formation and reduced contact between the Ta-hydride powders and air by wetting them. Therefore, an optimum amount of ethanol addition and milling time can enhance the formation of additional Ta-hydrides, while preventing oxidation during milling. Highlights: Chemical and structural properties of Ta-hydride during mechanical milling are reported. Ethanol addition during milling of Ta-hydride enhanced hydrogen incorporation. Ta-hydride being milled in conventional dry atmosphere was easily oxidized.